(untitled) (Research, Society and Development, 2021)
The rational use of energy is being increasingly encouraged. In some countries, there are even subsidies for industries to adopt energy efficiency measures. One of the sectors with great opportunities for efficiency is sanitation, where a large part of energy consumption refers to pumping stations. The objective of this work is to demonstrate the consumption of electrical energy and possible reduction of electrical energy consumption in a sector of study of the Autonomous Water and Sewage Service (SAAE) of the municipality in the south of Minas Gerais. To determine the measures to be taken to reduce energy costs, it is necessary to perform a system diagnosis. For this, field trials were carried out. The study sector had an average expense of R 42,097.44/year due to water losses in the system. When considering only electricity costs, they represent 34.20% of the costs in relation to water losses (R 14,395.90/year). The system presented 27.73% of total water losses, an energy consumption of 0.6627 kWh/m³ only for the R3 pumping station and 1.302 kWh/m³ when also considering the Water Collection and Treatment Plant (WTP).